2023
DOI: 10.14639/0392-100x-suppl.1-43-2023-08
|View full text |Cite
|
Sign up to set email alerts
|

Recurring benign paroxysmal positional vertigo after successful canalith repositioning manoeuvers

Abstract: SUMMARY Benign baroxysmal positional vertigo (BPPV) represents the most common peripheral vestibular dysfunction encountered in clinical practice. Although canalith repositioning procedures (CRPs) are a relatively successful treatment for BPPV, many patients suffer from recurrences. Several studies have demonstrated that various pathological conditions (diabetes, hypertension, endolymphatic hydrops, low vitamin D levels) as well as delayed BPPV treatment using CRP, multiple canal involvement may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A recent study from Italy reported that migraine is one of the risk factors for the recurrence of BPPV following successful canalith repositioning procedures (CRPs) [31]. Other risk factors for recurrence reported by the same study include female gender, age, hyperlipidemia, diabetes mellitus, hypertension, osteoporosis, vitamin D deficiency, and vascular diseases [31].…”
Section: • Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Italy reported that migraine is one of the risk factors for the recurrence of BPPV following successful canalith repositioning procedures (CRPs) [31]. Other risk factors for recurrence reported by the same study include female gender, age, hyperlipidemia, diabetes mellitus, hypertension, osteoporosis, vitamin D deficiency, and vascular diseases [31].…”
Section: • Causesmentioning
confidence: 99%
“…Other factors that they mentioned in Table 1 are risk factors for the occurrence and or recurrence of BPPV [31,35].…”
Section: Canalithiasis Of the Lateral Or Horizontal Canal Is More Seenmentioning
confidence: 99%